Importance of terminated groups in 9, 9-bis(4-methoxyphenyl)-substituted fluorene-based hole transport materials for highly efficient organic–inorganic hybrid and all-inorganic perovskite solar cells. Issue 17 (4th April 2019) - Zhang, Dongyang; Wu‡, Tai; Xu, Peng; Ou, Yangmei; Sun, Anxin; Ma, Huili; Cui, Bo; Sun, Hanwen; Ding, Liming; Hua, Yong
Abstract : Two fluorene-based HTMs have been synthesized for use in perovskite solar cells (PSCs). The (FAPbI3 )0.85 (MAPbBr3 )0.15 and CsPbI2 Br PSCs devices based on YT3 yield very impressive PCEs of 20.23% and 13.36%, respectively. Abstract : Hole-transport materials (HTMs) play a crucial role in determining the photovoltaic performance and long-term stability of perovskite solar cells (PSCs), because they not only efficiently facilitate hole-extraction and transfer, but also act as a barrier to protect the perovskite from moisture and oxygen. So far, the power conversion efficiencies (PCEs) over 20% in PSCs have been mostly achieved by employing aSpiro-OMeTAD -based HTM. However, it suffers from some drawbacks such as relatively low hole-mobility, complicated synthesis and difficult purification, which hamper its potential commercial applications. Here, for the first time, two new easily accessible 9, 9-bis(4-methoxyphenyl)-substituted fluorene-based HTMs comprising H (YT1 ) and methoxyphenyl-fluorene (YT3 ) as the terminated groups have been synthesized for use in organic–inorganic hybrid and all-inorganic PSCs. The (FAPbI3 )0.85 (MAPbBr3 )0.15 and CsPbI2 Br PSCs based onYT3 yield very impressive PCEs of 20.23% and 13.36%, respectively, both of which are higher than that ofSpiro-OMeTAD (19.18% and 12.30%). More encouragingly, theYT3 -based PSC displays good long-term stability for 600 hours. These results confirm that different terminated groups in HTMs show a significant effect on the energy levels, hole extraction and transfer, thin-film surface morphology and photovoltaic performance. Our findings could provide a useful insight for future rational design of HTMs for highly efficient and stable PSCs.